‘Should’ve known better’: Using Lerner’s Belief in a Just World to understand how the Fraud Justice Network observe victims of online romance and investment frauds - Nataraj-Hansen, Shalini (International review of victimology, 2024)
This article explores the application of Lerner’s Belief in a Just World (BJW) to online fraud. BJW finds that people tend to blame victims when their sense of justice is threatened and if there is little or no chance of obtaining compensation or justice for the victim. Specifically, BJW suggests that when victims are perceived as acting with agency, and have little chance of compensation, they are blamed for their crime. Online fraud victims are blamed by family, friends, justice agencies, and themselves, for their victimisation. Little is known about why the Fraud Justice Network (FJN), which comprises the multitude of agencies that aim to combat online fraud, blames victims. This article begins to address this gap by presenting findings of qualitative interviews with 14 FJN representatives, using thematic analysis. Three significant themes emerge about victims: ‘agency’, ‘gullibility and compensation’, and ‘deservedness of justice’. This study found that (a) victims are seen as behaviourally responsible, (b) agency is blameworthy, and (c) victims deserve justice. The study also finds evidence of BJW thinking within the FJN. Findings can inform future organisational policies on how victims of online fraud can be more effectively managed and supported, including by financial institutions or law enforcement agencies.